Necroptosis-driving genes RIPK1, RIPK3 and MLKL-p are associated with intratumoral CD3+ and CD8+ T cell density and predict prognosis in hepatocellular carcinoma - Akihiko Kawahara; Jun Akiba; Hirohisa Yano; Ambrogio Fassina; Rocco Cappellesso; Yoshiki Naito; Maria Guido; Paolo Simioni; Giuliana Cortese; Lorenzo Nicolè; Tiziana Sanavia; Valeria Maffeis; et al. (Journal for ImmunoTherapy of Cancer, 2022)
Background Hepatocellular carcinoma (HCC) is a highly lethal cancer and the second leading cause of cancer-related deaths worldwide. As demonstrated in other solid neoplasms and HCC, infiltrating CD8+ T cells seem to be related to a better prognosis, but the mechanisms affecting the immune landscape in HCC are still mostly unknown. Necroptosis is a programmed, caspase-independent cell death that, unlike apoptosis, evokes immune response by releasing damage-associated molecular factors. However, in HCC, the relationship between the necroptotic machinery and the tumor-infiltrating lymphocytes has not been fully investigated so far.Methods We investigated the association between the main necroptosis-related genes, that is, RIPK1, RIPK3, MLKL-p, and CD3+/CD8+ tumor-infiltrating T cell by RNA-seq data analysis in 371 patients with primary HCC from The Cancer Genome Atlas and then by immunohistochemistry in two independent cohorts of HCC patients from Italy (82) and Japan (86).Results Our findings highlighted the immunogenetic role of necroptosis and its potential prognostic role in HCC: RIPK1, RIPK3 and MLKL-p were found significantly associated with intratumoral CD3+ and CD8+ T cells. In addition, multivariate survival analysis showed that the expression of RIPK1, RIPK3 and MLKL-p was associated with better overall survival in the two independent cohorts.Conclusions Our results confirmed the immunogenetic properties of necroptosis (NCP) in human HCC, showing that tumor-infiltrating lymphocytes (TILs) and, specifically, CD8+ T cells accumulate in tumors with higher expression of the necroptosis-related genes. These results suggest the importance of further studies to better assess the specific composition, as well as the functional features of the immune environment associated with a necroptotic signature in order to explore new possible diagnostic and immunotherapeutic scenarios.